Comparative study of controllers for a cascade boost converter - Goh, Damian Jun Kai (2018)
The objective of this project is to design and implement a cascade boost converter with different feedback controllers. There are a total of 3 controllers presented, hysteresis sliding mode controller, non-adaptive current mode controller and adaptive current mode controller. Different test will be conducted to analyze the performance of each controller and the results will be presented and discussed. Finally, a comparison is conducted to recommend the best controller for the cascade boost converter.